Algoritma Media Sosial dan Pengaruhnya terhadap Pola Pikir Keagamaan Siswa MAN 1 Medan (Studi pada Konten Dakwah Pendek) - Syti Salwaa Nafiisah; Azril Arfansyah; Shaqila Rahmayani Gultom; Ridho Affandi; Umar Mukhtar Siregar (AN-NASHIHA Journal of Broadcasting and Islamic Communication Studies, 2026)
The rapid development of social media technology, particularly through algorithm-based content recommendation systems, has significantly transformed the distribution and consumption of religious information among adolescents. These algorithms personalize content exposure based on users’ interactions, preferences, and engagement patterns, thereby increasing the visibility of short-form da’wah content on platforms such as TikTok, Instagram Reels, and YouTube Shorts. This study aims to examine the influence of social media algorithms on the religious mindset of students at MAN 1 Medan, focusing on how exposure to short-form religious preaching content shapes their understanding, attitudes, and responses toward religious issues. Employing a quantitative research approach with a survey method, data were collected through structured questionnaires distributed to students and analyzed descriptively to identify patterns of digital engagement and their relationship with religious cognition. The findings indicate that algorithm-driven content recommendations play a meaningful role in directing students’ access to particular religious narratives, which subsequently contributes to the formation and reinforcement of their religious perspectives. These results highlight that social media functions not only as a communication platform but also as a digital environment that actively influences the development of religious thought among young users in the contemporary digital era.